Инновационное правовое обучение - Разуваева, М.В. (My University, 2016)
One of the parts of the state politics is the legal regulation of scientific and educational activity. Innovations in the sphere of law education might be observed in the context as one of educational institutions so as in whole state.
Keywords: state; state policy; legal training; education; innovative technologies